A Single Mass Gathering Resulted in Massive Transmission of COVID-19 Infections in Malaysia with Further International Spread - Mat, Nor Fazila Che (J Travel Med, 2020)
Malaysia has recorded the highest number of COVID-19 cases in Southeast Asia with more than 35% of new COVID-19 cases linked to the Sri Petaling gathering, a Moslem missionary movement attended by more than 19 000 people of different nationalities, in March 2020 in Kuala Lumpur. From this cluster, 1701 samples have been tested positive out of 21 920 tests carried out. Thus, mass gathering during COVID-19 pandemic period should be banned to curb disease transmission.